Abordagens cromatográficas para purificação da proteína NS1 nativa do virus da dengue sorotipo II (DENV-2) - Estrázulas, Tiago Severo (2018)
Dengue virus (DENV) is an arbovirus of the Flaviviridae family and has four different viral serotypes, such as DENV-1, DENV-2, DENV-3 and DENV-4. The virus codes for seven non-structural proteins responsible for virus replication within the host. Among them, the nonstructural protein (NS1), is important in the early diagnosis of virus infection in the body of infected patients, since it circulates in high blood levels during the acute phase of the disease. DENV is responsible for a variety of clinical manifestations in various parts of the world and currently infects around 100 million people. However, several obstacles are encountered regarding the correct identification of virus symptoms and their early diagnosis. Thus, the present work sought to obtain a high purity in the native form of the virus through a chromatographic protocol for purification of the NS1 nonstructural protein native to the Dengue serotype II virus originating from the culture medium of infected cells (Vero cells). In all, seven culture media were produced, with different volumes and concentrations. Due to the low initial concentration of these samples, sample concentration steps were carried out with membrane filtration and lyophilization. For NS1 purification studies, ion exchange chromatography techniques were used, with Hitrap QFF column and Hitrap Concanavalin A column affinity chromatography and Procion Red MX-5B dye immobilized the Chitosan Alginate Epoxidate (QAE) matrix, acting as matrix of pseudobiospecific affinity. The best adsorption profile of NS1 was obtained with the use of affinity columns, due to their higher specificity with the protein of interest and the tests performed with the Hitrap Concanavalin A column and the PR-MX5B-QAE dye showed a higher retention of NS1, with partial removal of proteins present in the initial crude sample. For the adsorption of this protein, the best adsorption results were found in the NS1-DENV2 A2 sample, in the gradient gradient 35 min (presence of 6 samples containing the NS1 in the elution step - about 50% of samples eluted from the column) and linear 30 min (presence of 5 samples containing NS1 - about 40% of the samples eluted). However, the conditions favored the adsorption of almost all the proteins present in the initial sample, such as albumin.